2023
DOI: 10.1021/acs.jafc.2c06658
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acid–Amino Acid Adducts Exert Distinct Immunomodulatory Effects in Macrophages Compared to Parent Phenolic Acids

Abstract: Caffeic acid (CA) and chlorogenic acid (CGA) are commonly found phenolic acids in plant-derived foods and beverages. Their corresponding adducts with cysteine (Cys) have been detected in coffee-containing beverages. However, despite the well-documented antioxidant and anti-inflammatory activity of CA and CGA, the immunomodulatory activities of the Cys adducts (CA–Cys and CGA–Cys) are unknown. The adducts were therefore synthesized, and their immunomodulatory effects were studied in lipopolysaccharide (LPS)-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A study suggested that chlorogenic acid and baicalin are the biologically active ingredients in honeysuckle and scutellaria, respectively. Some in vitro studies demonstrated that chlorogenic acid helped alleviate the LPS-induced inflammatory response in macrophages [ 7 , 8 ]. Chlorogenic acid reduced the damage to vascular endothelial cells caused by acute increases in the Nitric oxide(NO) levels in intestinal mucosal microvascular endothelial cells that were challenged with LPS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study suggested that chlorogenic acid and baicalin are the biologically active ingredients in honeysuckle and scutellaria, respectively. Some in vitro studies demonstrated that chlorogenic acid helped alleviate the LPS-induced inflammatory response in macrophages [ 7 , 8 ]. Chlorogenic acid reduced the damage to vascular endothelial cells caused by acute increases in the Nitric oxide(NO) levels in intestinal mucosal microvascular endothelial cells that were challenged with LPS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the demonstrated expression of pro-inflammatory IL-1β , IL-6 , and TNF-α in LPS-induced RAW 264.7 cells at the mRNA level and the results of our analysis of downstream signaling molecules, a cytokine array was performed. Based on the GSE206519 database set [ 24 ], 26 cytokines were upregulated, and 7 cytokines were downregulated in LPS-induced RAW 264.7 cells ( Figure 6 a–c and Figure S1 ). Both COD and sabinene downregulated five cytokines: IL-1β, IL-6, IL-27, granulocyte–macrophage colony-stimulating factor (GM-CSF), and IL-1 receptor antagonist (IL-1ra) ( Figure 6 d).…”
Section: Resultsmentioning
confidence: 99%
“…It's biologically plausible. Recent studies have found that protein-polyphenol interactions may enhance the antiinflammatory activity of phenolic compounds [35,36]. Additionally, milk proteins may possess renal-protective functions, such as suppressing the angiotensin converting enzyme and lowering blood pressure, through peptides (casokinins and lactokinins) that have vasoactive properties [37][38][39].…”
Section: Discussionmentioning
confidence: 99%